2022
DOI: 10.1002/ange.202115819
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Electrochemistry of Single Plasmonic Nanoparticles

Abstract: The structure-function relationship of plasmonenhanced electrochemistry (PEEC) is of great importance for the design of efficient PEEC catalysts, but is rarely investigated at single nanoparticle level for the lack of an efficient nanoscale methodology. Herein, we report the utilization of nanoparticle impact electrochemistry to allow single nanoparticle PEEC, where the effect of incident light on the plasmonic Ag/Au nanoparticles for accelerating cobalt metalorganic framework nanosheets (Co-MOFNs) catalyzed h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 42 publications
(38 reference statements)
0
4
0
Order By: Relevance
“…A single-nanoparticle collision electrochemistry (SNCE) biosensor (SNCEB) based on the SNCE electrocatalytic mode for the detection of the H7N9 avian influenza virus (AIV) was recently reported [173]. It is to be underlined that SNCE is confirmed as a promising nanoparticle-based analytical method [174]. Briefly, a constant potential is applied to an ultramicroelectrode (UME), immersed in a dilute solution of NPs.…”
Section: Aptasensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…A single-nanoparticle collision electrochemistry (SNCE) biosensor (SNCEB) based on the SNCE electrocatalytic mode for the detection of the H7N9 avian influenza virus (AIV) was recently reported [173]. It is to be underlined that SNCE is confirmed as a promising nanoparticle-based analytical method [174]. Briefly, a constant potential is applied to an ultramicroelectrode (UME), immersed in a dilute solution of NPs.…”
Section: Aptasensorsmentioning
confidence: 99%
“…Owing to the Brownian motions, stochastic collisions of the NPs occurred at the surface of the UME, causing transient electrochemical signals. [174] Considering the different ways of interaction between nanoparticles and the UME, the SCNE strategies can be divided into three conventional categories according to the electrochemical process: blocking, electrocatalytic, and particle self-electrolysis. In particular, in the electrocatalytic mode, [175][176][177] the catalytically active NPs are present in the solution, producing electrocatalytic processes at the UME surface.…”
Section: Aptasensorsmentioning
confidence: 99%
“…Although few pioneer works have been conducted, the performance is not quite satisfactory, and the mechanism still needs to be carefully investigated. For example, reactive oxygen species (ROSs) were the main oxidants in the bipolar electrode process, but their production ability was limited. , The effect of the electric field on the electrochemical behaviors of conducting materials remains a long-term dispute: monopolar electrode versus bipolar electrode. , Therefore, we aimed to address the above-mentioned scientific and practical issues in this work.…”
Section: Introductionmentioning
confidence: 99%
“…Upon collision of single Ag/Au nanoparticles under irradiation, increased catalytic currents were observed that have been attributed to hot carrier injection from Ag/Au nanoparticles to Co-MOF, leading to a lowering of the reaction activation energy. 24 Here, we use nano-impact SEE to investigate glucose electrooxidation on gold nanoparticles at the single-particle level in a pure plasmon metal system. We first measure hot carrier dynamics in AuNPs under experimental conditions using transient absorption spectroscopy (TAS).…”
Section: Introductionmentioning
confidence: 99%